Cardioprotective effects of gypenoside XVII against ischemia/reperfusion injury: Role of endoplasmic reticulum stress, autophagy, and mitochondrial fusion fission balance. (27th May 2022) - Su, Shijia; Wang, Jiarui; Wang, Jing; Yu, Ruili; Sun, Likang; Zhang, Yue; Song, Lei; Pu, Weiling; Tang, Yi; Yu, Yingli; Zhou, Kun
Abstract: Gypenoside XVII (GP‐17), a tetracyclic triterpene saponin isolated from the functional food Gynostemma pentaphyllum, has been demonstrated protective effects against cerebrovascular and cardiovascular diseases on multiple disease models. In this study, we established a myocardial infarction (MI) model by ligating the left anterior descending coronary artery, and explored whether GP‐17 prevent myocardial ischemia/reperfusion (I/R) injuries in mice. Compared with the I/R group, GP‐17 significantly improved the cardiac function, reduced the MI, decreased myocardial pathology, activated superoxide dismutase and catalase, and reduced the content of lactate dehydrogenase, creatine kinase, malondialdehyde, and inflammatory factor. The proteomic analysis showed multiple differential proteins between the GP‐17 and I/R groups enriched in endoplasmic reticulum and mitochondria. Western‐Blot showed that GP‐17 significantly decreased the expression of GRP78, ATF6, CHOP, and phosphorylation of PERK, indicating the inhibition of ERS. GP‐17 inhibited the expression of ATG5, LC3A/B, and BAX, illustrating the suppression of autophagy and apoptosis. Moreover, both GP‐17 and 4‐PBA could improve the downregulated Mfn2, meaning that inhibition of ERS regulated the mitochondrial fusion fission balance, thus protected the function of mitochondria. In conclusion, we found that GP‐17 prevented against myocardial I/R injury by inhibit ERS‐induced cell apoptosis, autophagy, oxidative stress, and mitochondrial division.